Dari Yoshida Doctrine ke Fukuda Doctrine: Politik Luar Negeri Jepang di Asia Tenggara Pasca-Perang Dunia II - Purbantina, Adiasri Putri (Global and Policy Journal of International Relations, 2013)
ABSTRACTJapan’s foreign policy in Southeast Asia in the postwar era was based on Yoshida Doctrine. After her lost in World War II, Prime Minister Yoshida Shigeru declared that economic development will be Japan’s priority. At that time, Japan’s interest on Southeast Asia especially was related to raw materials as one of the tools to build her economy. However, the use of this economic diplomacy created several anti-Japanese movements in some Southeast Asia Countries. In 1977, Prime Minister Fukuda Takeo came to the 10th ASEAN Anniversary and declared that Japan has no intention to be the next hegemonic power in the region. Thus he formed a new framework for Japan’s foreign policy which based on “heart to heart understanding” and added cultural approach into it.Keywords: economic diplomacy, cultural approach.DOI:https://doi.org/10.33005/jgp.v1i01.2009